ALDH1A3 Coordinates Metabolism With Gene Regulation in Pulmonary Arterial Hypertension. Issue 21 (25th March 2021) - Li, Dan; Shao, Ning-Yi; Moonen, Jan-Renier; Zhao, Zhixin; Shi, Minyi; Otsuki, Shoichiro; Wang, Lingli; Nguyen, Tiffany; Yan, Elaine; Marciano, David P.; Contrepois, Kévin; Li, Caiyun G.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Metabolic alterations provide substrates that influence chromatin structure to regulate gene expression that determines cell function in health and disease. Heightened proliferation of smooth muscle cells (SMC) leading to the formation of a neointima is a feature of pulmonary arterial hypertension (PAH) and systemic vascular disease. Increased glycolysis is linked to the proliferative phenotype of these SMC. Methods: RNA sequencing was applied to pulmonary arterial SMC (PASMC) from PAH patients with and without a BMPR2 (bone morphogenetic receptor 2) mutation versus control PASMC to uncover genes required for their heightened proliferation and glycolytic metabolism. Assessment of differentially expressed genes established metabolism as a major pathway, and the most highly upregulated metabolic gene in PAH PASMC was aldehyde dehydrogenase family 1 member 3 ( ALDH1A3), an enzyme previously linked to glycolysis and proliferation in cancer cells and systemic vascular SMC. We determined if these functions are ALDH1A3-dependent in PAH PASMC, and if ALDH1A3 is required for the development of pulmonary hypertension in a transgenic mouse. Nuclear localization of ALDH1A3 in PAH PASMC led us to determine whether and how this enzyme coordinately regulates gene expression and metabolism in PAH PASMC. Results: ALDH1A3 mRNA and protein were increased in PAH versus control PASMC, and ALDH1A3 was required for their highly proliferative and glycolytic properties. Mice with Aldh1a3 deleted in SMC did not develop hypoxia-induced pulmonary arterial muscularization or pulmonary hypertension. Nuclear ALDH1A3 converted acetaldehyde to acetate to produce acetyl coenzyme A to acetylate H3K27, marking active enhancers. This allowed for chromatin modification at NFYA (nuclear transcription factor Y subunit α) binding sites via the acetyltransferase KAT2B (lysine acetyltransferase 2B) and permitted NFY-mediated transcription of cell cycle and metabolic genes that is required for ALDH1A3-dependent proliferation and glycolysis. Loss of BMPR2 in PAH SMC with or without a mutation upregulated ALDH1A3, and transcription of NFYA and ALDH1A3 in PAH PASMC was β-catenin dependent. Conclusions: Our studies have uncovered a metabolic-transcriptional axis explaining how dividing cells use ALDH1A3 to coordinate their energy needs with the epigenetic and transcriptional regulation of genes required for SMC proliferation. They suggest that selectively disrupting the pivotal role of ALDH1A3 in PAH SMC, but not endothelial cells, is an important therapeutic consideration.